Effect of resveratrol or ascorbic acid on the stability of α-tocopherol in O/W emulsions stabilized by whey protein isolate: Simultaneous encapsulation of the vitamin and the protective antioxidant. (1st April 2016) - Wang, Lei; Gao, Yahui; Li, Juan; Subirade, Muriel; Song, Yuanda; Liang, Li
Highlights: α-Tocopherol was encapsulated in the oil phase of WPI stabilized emulsions. Resveratrol was bound at the oil–water interface of WPI stabilized emulsions. Protective effect against α-tocopherol decomposition increased with protein concentration. Influence of ascorbic acid in the continuous aqueous phase depended on concentration. Resveratrol improved the stability of α-tocopherol, attributed mainly to the cis -isomer. Abstract: Food proteins have been widely used as carrier materials due to their multiple functional properties. Hydrophobic bioactives are generally dissolved in the oil phase of O/W emulsions. Ligand-binding properties provide the possibility of binding bioactives to the protein membrane of oil droplets. In this study, the influence of whey protein isolate (WPI) concentration and amphiphilic resveratrol or hydrophilic ascorbic acid on the decomposition of α-tocopherol in the oil phase of WPI emulsions is considered. Impact of ascorbic acid, in the continuous phase, on the decomposition depended on the vitamin concentration. Resveratrol partitioned into the oil–water interface and the cis -isomer contributed most of the protective effect of this polyphenol. About 94% of α-tocopherol and 50% of resveratrol were found in the oil droplets stabilized by 0.01% WPI. These results suggest the feasibility of using the emulsifying and ligand-binding properties of WPI to produce carriers for simultaneous encapsulation of bioactives with different physicochemical properties.